A review of PEM fuel cell durability: materials degradation, local heterogeneities of aging and possible mitigation strategies. Issue 6 (5th March 2014) - Dubau, Laetitia; Castanheira, Luis; Maillard, Frédéric; Chatenet, Marian; Lottin, Olivier; Maranzana, Gaël; Dillet, Jérôme; Lamibrac, Adrien; Perrin, Jean‐Christophe; Moukheiber, Eddy; ElKaddouri, Assma; De Moor, Gilles; et al.
<x xml:space="preserve">Abstract</x> Through a tight collaboration between chemical engineers, polymer scientists, and electrochemists, we address the degradation mechanisms of membrane electrode assemblies (MEAs) during proton exchange membrane fuel cell (PEMFC) operation in real life (industrial stacks). A special attention is paid to the heterogeneous nature of the aging and performances degradation in view of the hardware geometry of the stack and MEA. Macroscopically, the MEA is not fuelled evenly by the bipolar plates and severe degradations occur during start‐up and shut‐down events in the region that remains/becomes transiently starved in hydrogen. Such transients are dramatic to the cathode catalyst layer, especially for the carbon substrate supporting the Pt‐based nanoparticles. Another level of heterogeneity is observed between the channel and land areas of the cathode catalyst layer. The degradation of Pt3Co/C nanocrystallites employed at the cathode cannot be avoided in stationary operation either. In addition to the electrochemical Ostwald ripening and to crystallite migration, these nanomaterials undergo severe corrosion of their high surface area carbon support. The mother Pt3Co/C nanocrystallites are continuously depleted in Co, generating Co2+ cations that pollute the ionomer and depreciate the performance of the cathode. Such cationic pollution has also a negative effect on the physicochemical properties of the proton‐exchange membrane (proton conductivity and resistance to fracture), eventually leading to hole formation. These defects were localized with the help of an infrared camera. The mechanical fracture‐resistance of various perfluorosulfonated membranes further demonstrated that polytetrafluoroethylene‐reinforced membranes better resist hole formation, due to their high resistance to crack initiation and propagation. WIREs Energy Environ 2014, 3:540–560. doi: 10.1002/wene.113 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.